2010
DOI: 10.1007/s00330-010-1936-y
|View full text |Cite
|
Sign up to set email alerts
|

CT fluoroscopy-guided lung biopsy versus conventional CT-guided lung biopsy: a prospective controlled study to assess radiation doses and diagnostic performance

Abstract: CT fluoroscopy-guided NAB of pulmonary lesions provides high diagnostic accuracy and can be performed with significantly fewer complications. However, radiation exposure to both patient and doctor were significantly higher than conventional CT-guided NAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
127
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(137 citation statements)
references
References 28 publications
8
127
1
1
Order By: Relevance
“…In our series, we found three cases in which post-procedual CT showed a thin blood layer around the lesion. Adequacy rate of peripheral pulmonary or pleural lesion biopsy performed with a non fine needle is reported to be between 89.5% and 97% with CT guidance (6,9,10,23) and between 76%and 96 % with US guidance (17,19,20). Our values are comparable with those reported in the literature.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…In our series, we found three cases in which post-procedual CT showed a thin blood layer around the lesion. Adequacy rate of peripheral pulmonary or pleural lesion biopsy performed with a non fine needle is reported to be between 89.5% and 97% with CT guidance (6,9,10,23) and between 76%and 96 % with US guidance (17,19,20). Our values are comparable with those reported in the literature.…”
Section: Resultssupporting
confidence: 86%
“…These complications can increase patient discomfort , as well as the length of time during which the needle is positioned across the pleura . The introduction of CT fluoroscopy has overcome the limitation of real-time needle visualization during CT-guided procedures, but it still provides only transverse sections and introduces a substantial amount of radiation exposure to both patient and operator (6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A report by Manhire et al suggested that within TTNA, no association exists between complication rates and needle type and size [13]. TTNA has diagnostic yields of greater than 90%, which is higher than any other non-surgical approach [14] Other viable diagnostic options for indeterminate pulmonary lesions such as flexible bronchoscopy and its ancillary procedures have lower success rates ranging from (14-63%). [15] The disadvantages of TTNA however, are very high rates of pneumothorax (ranging between15-25%) while other bronchoscopic approaches have much lower rates (~1.5%).…”
Section: Introductionmentioning
confidence: 99%